Gastroesophageal reflux disease and paraneoplastic neurological syndrome associated with long‐term survival in limited stage small‐cell lung cancer. Issue 7 (23rd February 2022) - Ernani, Vinicius; Du, Lin; Ross, Helen J.; Yi, Joanne E.; Wampfler, Jason A.; Schild, Steven E.; Xie, Hao; Swanson, Karen L.; Tazelaar, Henry D.; Yang, Ping
Abstract: Introduction: Patients with s mall‐cell lung cancer (SCLC) have a very poor prognosis. However, a subset of SCLC achieves long‐term survival. The objective of this study was to investigate factors and pattern of long‐term survival in patients with limited‐stage small cell lung cancer (LS‐SCLC) who achieved a complete response (CR) after chemoradiotherapy. Patient and Methods: This was a single‐center retrospective study. The analysis of hazard ratio (HR) and 95% confidence interval (CI) was performed using Cox proportional hazards model. For pattern analysis, the date of recurrence was used as the endpoint. The nominal categorical variables were analyzed by the χ 2 test. Survival was estimated using the Kaplan–Meier model, and the results were reported as the median and interquartile range. Results: We identified 162 patients, median age was 64.7 (56.2–70.2) years, and 94 (58%) were females. Eighty‐one patients (50%) had recurrence during follow‐up. Gastroesophageal reflux disease (GERD) (HR, 0.65; 95% CI, 0.45–0.93; p  = 0.016) and neurological paraneoplastic syndrome (PNS) (HR, 0.46; 95% CI, 0.29–0.72; p  < 0.001) were independent factors associated with improved overall survival (OS). Patients with GERD had prolonged recurrence free survival (RFS) compared to patients without GERD (median, 29.1 months vs. 13.9 months, p  < 0.001), whereas patients with neurological PNS had a reduced recurrence rate compared to those patients without neurological PNS (No. [%], 8 [20.5] vs. 73 [59.3], p  < 0.001). Conclusions: Patients with LS‐SCLC achieving a CR after chemoradiotherapy, GERD, and neurological PNS were associated with improved OS. GERD and neurological PNS were associated with longer RFS and lower recurrence rate, respectively. Abstract : Hypothetical association between gastroesophageal reflux disease (GERD) and long‐term survival of small cell lung cancer (SCLC): Pathway 1: Paraneoplastic endocrine hormone induces GERD while inhibiting SCLC. Pathway 2: Proton pump inhibitor (PPI) is an anti‐cancer drug. Pathway 3: Paraneoplastic antibody causes GERD and increases curative effect of chemo‐ and radiation therapy